A Study On The Relationship Between Customer Satisfaction And The Implementation Of Total Quality Management Concept In The Malaysian Telecommunication Industry - Hishamuddin Ismail, (2001)
In today's globalization, quality and productivity had become the major concern for companies to survive. Customers is the main focus for any successful business in which customer satisfaction models had become the most important tools to win the customer in the competitive marketplace. This study will analyze to which extent the implementation of quality management instrument did have some impact on the customer satisfaction level. This study will be focusing on the telecommunication industry since this industry will play a pivotal role in the information technology (IT) era. This study will be utilizing the SERQUAL method (Parasuraman, Ziethaml, Berry, 1998), technical and functional quality ( Gronross, 1990) and service performance factors ( Cronin & Taylor, 1992) to test the current level of service quality particularly for Digitaline II. Based on the study, it is found that there is a significant relationship between the customer satisfaction and implementation of service quality. The finding suggested that reliability dimension of SERVQUAL that comprises of three elements I.e. fault reporting center, response time and restoration time have strong correlation with the customer satisfaction. Similarly, the result also indicated that the technical dimension of service quality appear to has the stronger impact on customer satisfaction as compared to functional quality. The finding in this study also confirmed and proved that the high level of customer satisfaction is not the answer for customer loyalty. This finding is inline with other finding (Mittal & Lassar, 1998; Elnan & Andersen, 1999) that found no correlation between the customer satisfaction and customer loyalty. However, the empirical testing found six variables that are significantly correlated with customer loyalty.